Enhancing Creativity: The Role of Affective Commitment and Knowledge Sharing - Noerchoidah; Dhyah Harjanti; I Made Dwiarta; Widjojo Suprapto (Journal of Business and Management Review, 2023)
As higher education institutions were facing strong competition to attract new coming students, the contributions of lecturers were acknowledged as one of the driving resources of the university’s competitive advantage. Besides teaching, all lecturers were required to conduct research and social services. While fulfilling these tasks, some lecturers focused on one aspect only and neglect the others. This situation created a disparity in lecturers’ creative mindsets, as they keep on doing similar tasks repeatedly. Creativity developed by the lecturers could become the competitive advantage of their university. The objective of this study was to examine how lecturers’ creativity is constructed. Two influencing factors, which are affective commitment and knowledge sharing, were tested to see their influences on creativity. The data were collected from 170 randomly selected lecturers of private universities who obtained an “A” accreditation. Since this was quantitative research, the collected data were processed with the Partial Least Square technique. The results showed that lecturers’ creativity was significantly affected by knowledge sharing as well as affective commitment. However, knowledge sharing did not mediate the relationship between affective commitment and creativity.